ANALISIS POS-POS DALAM PAJAK DAERAH YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH DKI JAKARTA TAHUN 2010-2012 - Belinda Christy Sutanto; Vivi Adeyani Tandean (Jurnal Akuntansi Bisnis, 2017)
Regional autonomy is the right, authority, and responsibility to manage and administer own governmental matter. To run regional autonomy fully, it is essential that each district has the ability to minimise its dependence on the central government, where monetary independence becomes an important criterion to know the capability of a district to manage and administer its own area. Local tax is one of the components of own-source revenue which has the potential and considerable contribution towards revenue. Local tax which is collected is adapted with the characteristics and potentials from each district. The central place that Special Capital City District Jakarta holds as the economic, politic and cultural centre results in the high potential revenue contributed by the vehicle tax and hotel tax. The tax contribution and tax effectivity towards the own-source revenue will show that whether the related taxes have the potential to be more optimised. The object of this research is the own-source revenue, vehicle tax, and hotel tax. The method of research used is statistic study, using descriptive research design. The data collection technique used in this research is utilising secondary data collected from government institutions. The results of this research show that the total average of vehicle tax and hotel tax are greater than the increase in motor vehicle amount and hotel occupancy rate. Realisation of motor vehicle tax and hotel tax has a greater percentage average compared to the budget of motor vehicle tax and hotel tax. Additionally, vehicle tax and hotel tax also contribute considerably towards the own-source revenue.The conclusion from this research is that the motor vehicle tax and hotel tax are good sources of local tax. Motor vehicle tax and hotel tax have a good rate of increase. Additionally, motor vehicle tax and hotel tax also have positive average of tax effectivity, and also give considerably large contributions towards own-source revenue. Keywords: Own-source Revenue, Vehicle Tax, Hotel Tax, Effectivity, Contributions